2021
DOI: 10.51359/2526-7884.2021.249263
|View full text |Cite
|
Sign up to set email alerts
|

Valores Pessoais no Consumo de Cafés em Cápsula

Abstract: A pesquisa buscou identificar os valores pessoais que orientam o comportamento dos consumidores de cafés em cápsulas, e discuti-los sob às perspectivas da teoria de valores pessoais. Trata-se de uma pesquisa qualitativa, descritiva, a qual utilizou-se das técnicas projetivas, conclusão de frase e foto-elicitação, em conjunto à técnica de entrevista em profundidade Laddering. Para análise dos dados e resultados, foi utilizado o software LadderUX. Os resultados identificaram os valores: benevolência de cuidado, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The use of Gutman's (1982) means-end chain theory made it possible to identify the relationships between attributes and consequences (means) and desired personal values (end), and through the correlation with Schwartz's (2017) human values theory it was possible to describe the values found in the content analysis of the interviews with consumers of specialty coffees; this confirms the importance of using theories that have theoretical alignment within the theoretical framework of marketing and consumer behavior, as already demonstrated in other studies (Gandia et al, 2018;Castro et al, 2019;Teodoro et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The use of Gutman's (1982) means-end chain theory made it possible to identify the relationships between attributes and consequences (means) and desired personal values (end), and through the correlation with Schwartz's (2017) human values theory it was possible to describe the values found in the content analysis of the interviews with consumers of specialty coffees; this confirms the importance of using theories that have theoretical alignment within the theoretical framework of marketing and consumer behavior, as already demonstrated in other studies (Gandia et al, 2018;Castro et al, 2019;Teodoro et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…Studies on consumer behavior in relation to food consumption also used the theory proposed by Schwartz, demonstrating both academic and managerial coherence and applicability (Ha and Jang, 2013;Gandia et al, 2018;Castro et al, 2019;Teodoro et al, 2021). These studies have identified consumption motivations and perceptions linked to consumers' personal values, as well as the theory's compatibility with other academic perspectives such as consumer sensitivity toward the brand or the consumer environment (Ha and Jang, 2013;Gandia et al, 2018), the correlation in the formation of the individual's identity (Castro et al, 2019) and conscious and sustainable consumption (Teodoro et al, 2021).…”
Section: Consumption Motivated By Personal Valuesmentioning
confidence: 99%
See 1 more Smart Citation